Concrete Paver Blocks using Particles Replacement Expanded Polystyrene Beads and Addition of Coir Fibre - Abdul Rahman, Muhammad Firdaus Nabhan; Sarif, Abd Sukor (Progress in Engineering Application and Technology, 2026)
This study evaluates the incorporation of Expanded Polystyrene Beads (EPS) and Coir Fiber (CF) in the production of interlocking concrete paver blocks. Four mix designs were developed, 0%, 10%, 20% and 30% EPS replacing coarse aggregate by weight while addition of, 0%, 1%, 2% and 3% CF. Compressive strength, water absorption and density were assessed at 7 and 28 days. The results show diminish in early strength with higher EPS, though long-term curing improved durability. Appropriate performance was observed in the 10%-20% EPS and 1%-2% CF range. These findings support the development of making sustainable interlocking concrete paver blocks materials using natural and industrial waste.